Soil microbiome composition is highly responsive to precipitation and plant composition manipulations in a field biodiversity experiment - Burrill, Haley M.; Magnoli, Susan M.; Bever, James D. (Frontiers in Microbiomes, 2025)
IntroductionClimate change and plant biodiversity loss have large impacts on terrestrial ecosystem function, with the soil microbiome being primary mediators of these effects. The soil microbiome is a complex system, consisting of multiple functional groups with contrasting life histories. Most studies of climate forces and plant biodiversity effects on microbiome consider the perturbations and the microbial functional groups in isolation preventing us from understanding the full picture of the relative and differential impacts of perturbations on microbial functional groups.MethodsWe measured changes in multiple microbial communities with different functionality, including plant mutualists and pathogens, after three growing seasons in a full-factorial experiment manipulating precipitation (50%, 150% of ambient), plant diversity, and plant composition. Using amplicon sequencing to characterize the response of fungi, arbuscular mycorrhizal fungi, bacteria and oomycetes, and we found that composition of all microbial groups differentiated strongly between precipitation treatments.ResultsOomycete and bacterial diversity increased with 150% precipitation, while AM and saprotroph fungal diversity decreased. Microbial differentiation in response to plant family and plant species composition was stronger after the third growing season than observed after year one. However, microbial response to plant species richness was weaker in year three. Microbiome response to plant composition was largely independent of the response to precipitation, except for oomycetes, which had greater response to plant composition in high precipitation.DiscussionThese findings build upon prior findings that these microbial community members differentially respond to plant community compositional treatments, by measuring the response over 3 years and with the addition of precipitation treatments. We find that both changes in climate and plant composition can drive major differences in soil microbiome composition, which can feed back on plant community structure and alter ecosystem function.